On the dynamic response of fluid-filled buried pipelines - Mishra B.K.; Upadhyay P.C. (My University, 2025)
This paper presents a theoretical analysis of the axisymmetric steady state dynamic response of buried fluid-filled pipelines excited by seismic waves travelling in the surrounding infinite medium (soil). An infinite cylindrical shell model including the rotary inertia and shear deformation effects, has been used for the pipeline. Comparisons of the numerical results for a fluid-filled shell with those for an empty shell show that the presence of the fluid suppresses the response at some wavelengths but augments it at others. The overall response of the fluid-filled shell is observed to be quite different from that of the empty shell, and this difference is found to be more pronounced in softer soil conditions. © 1987.